Heterogeneous occurrence of evergreen broad-leaved forests in East Asia: Evidence from plant fossils - Jiagang Zhao; Shufeng Li; Jian Huang; Wenna Ding; Mengxiao Wu; Tao Su; Alexander Farnsworth; Paul J. Valdes; Linlin Chen; Yaowu Xing; Zhekun Zhou (Plant Diversity)
Evergreen broad-leaved forests (EBLFs) are widely distributed in East Asia and play a vital role in ecosystem stability. The occurrence of these forests in East Asia has been a subject of debate across various disciplines. In this study, we explored the occurrence of East Asian EBLFs from a paleobotanical perspective. By collecting plant fossils from four regions in East Asia, we have established the evolutionary history of EBLFs. Through floral similarity analysis and paleoclimatic reconstruction, we have revealed a diverse spatio-temporal pattern for the occurrence of EBLFs in East Asia. The earliest occurrence of EBLFs in southern China can be traced back to the middle Eocene, followed by southwestern China during the late Eocene–early Oligocene. Subsequently, EBLFs emerged in Japan during the early Oligocene and eventually appeared in central-eastern China around the Miocene. Paleoclimate simulation results suggest that the precipitation of wettest quarter (PWetQ, mm) exceeding 600 mm is crucial for the occurrence of EBLFs. Furthermore, the heterogeneous occurrence of EBLFs in East Asia is closely associated with the evolution of the Asian Monsoon. This study provides new insights into the occurrence of EBLFs in East Asia.